2021
DOI: 10.58629/mjms.v35i1.30
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trace Elements Lead, Nickel and Cadmium in Ground Water from Wells near Southern Refineries, Basrah-Iraq

Abstract: The current study was conducted to estimate the concentrations of three trace elements; nickel, lead and cadmium in the groundwater of eight wells, the six wells from w1 to w6 were close to the refineries at about half a kilometer to three kilometers and w7 and w8 wells were about 12.5 km away from the area (control wells) in the surrounding area of Southern Refineries (Al-Shuaiba), Al-Zubair district, Basrah Governorate, southern Iraq. Water samples were collected quarterly. The highest concentrations of lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The highest value of pH reached to 8.78 in well W7. The lowest value reached to 7.21in well W5, Carbon dioxide in the water, and this increase can be explained on the basis of the amount of dissolved salts as the increase in water salts then increases its acidic function and thus it is basic and the results showed that the concentrations pH was accompanied by an increase in the amount of salts, and this is in accordance with the study [20]. This is confirmed by the results of the statistical analysis of the existence of a positive significant correlation between the pH and salinity at a probability level (P <0.01).…”
Section: Physical and Chemical Properties: -supporting
confidence: 89%
See 1 more Smart Citation
“…The highest value of pH reached to 8.78 in well W7. The lowest value reached to 7.21in well W5, Carbon dioxide in the water, and this increase can be explained on the basis of the amount of dissolved salts as the increase in water salts then increases its acidic function and thus it is basic and the results showed that the concentrations pH was accompanied by an increase in the amount of salts, and this is in accordance with the study [20]. This is confirmed by the results of the statistical analysis of the existence of a positive significant correlation between the pH and salinity at a probability level (P <0.01).…”
Section: Physical and Chemical Properties: -supporting
confidence: 89%
“…The wells of the current study exceeded the permissible values in (Iraqi drinking water standards, [13], and the global [14, [15], [16] proposed for drinking water of 250 mg / L. The results of in electrical conductivity the current study indicate that the highest value was recorded at 8.540 mS / cm in well W7, and the lowest value was 4.933 mS / cm in well W5. 0.01 r = 0.921, conductivity and chloride ion r = 0.930, P <0.01 and in the study of Labar Al-Zubair it was classified as unsuitable for human consumption depending on the values of electrical conductivity, dissolved salts and chloride ion [20], and may be due to the difference in the geological formations of the regions as they depend on the type of rocks and soils that are in contact with [21], the results of the study exceeded the permissible limits of 1600 microsmins / cm in (Iraqi drinking water standards [13], and [14], [15], [16]. The highest value of Total Dissolved Solids (TDS) reached to 8976 mg / l in well W7, and the lowest value reached to 3923 mg / l in well W5.…”
Section: Physical and Chemical Properties: -mentioning
confidence: 95%
“…The importance of most heavy elements in the living system is due to their ability to form complex organic compounds in addition for being active centers for a large number of enzymes so that they perform functions in the life system, despite their presence in very low concentration cover most of the element, and an excess or deficiency of these elements leads to physiological damage to the living organisms (Al-Saad et al, 2003). These elements are an important class of pollutants that have lethal effects and sub-lethal effects on living organisms (Younus and Al-Khafaji, 2020). There are two major sources of heavy metals in the aquatic environment of southern Iraq, natural and anthropogenic (Saleh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%